Enterovesical Fistula: A Rare Complication of Urethral Catheterization. (3rd August 2009) - Hawary, Amr; Clarke, Laurence; Taylor, Alasdair; Duffy, Peter
Abstract : This report describes the case of an eighty-two-year old lady with an indwelling urethral catheter inserted eight years prior to her presentation to manage her urinary incontinence. She underwent radiotherapy for muscle-invasive bladder cancer (stage T2b) in 1991 and had a laparotomy and drainage of an appendicular abscess in her early twenties. She presented with a short history of fecaluria, pneumaturia, and passage of urine per rectum. On laparotomy she was found to have an inflated catheter balloon that has eroded through the bladder wall into the lumen of a terminal ileal segment. To our knowledge this is the first reported case in literature of a patient developing an enterovesical fistula as a result of a urethral catheter eroding through the bladder wall into the bowel lumen. There are numerous known complications of long-term urethral catheterization. They include recurrent urinary tract infections, recurrent pyelonephritis, sepsis, urethral stricture, blocked and retained catheters, among many other reported complications. This case describes an unusual presentation secondary to an even more unusual complication. This should be considered when handling patients with indwelling urethral catheters inserted in unhealthy bladders.